Modern Legal Regulation of Inter-Budget VAT Distribution in the People’s Republic of China - D. Bachurin (BRICS Law Journal)
The work presents a comprehensive study of legal regulation of interbudgetary VAT distribution in the People’s Republic of China in the context of the country’s socio-economic development. Particular attention is paid to the analysis of financial decentralization and the distribution of income from value-added taxation at the municipal district level and the distribution of budget revenues in the provinces of the People’s Republic of China. Decentralized distribution of value added tax has a great impact on innovative development in the context of an imbalance in budget expenditures. The author makes a conclusion that one of the key factors for the success of Chinese reforms is the stimulation of provincial and local authorities to develop the economy by combining the expansion of budgetary powers with the administrative and disciplinary control methods. The harmonization of central functions and the separation of financial and legal powers between different levels of government allows Chinese authorities to focus on the following targets: (1) concentration of financial resources; (2) balanced regional development; (3) motivation of local authorities through decentralization; (4) effectiveness of financial control. The inter-budgetary distribution of VAT in China is one of the significant financial and legal instruments of effective socioeconomic policy. Modern legal regulation of inter-budgetary VAT distribution in the PRC is aimed at supporting industrial policy and expanding production capital based on the gradual transfer of the tax burden from production to consumption while maintaining stable budget revenues from value-added taxation.